Narcissus on vacation as a specular aesthetic experience of recognition: Caetano Veloso and his unsubmissive body - Laan Mendes de Barros; Marcos Roberto Souza Brogna (Dialogos, 2024)
Based on a theoretical-epistemological problematization that articulates communication and aesthetic experience, this article examines the documentary Narciso em Vacation. From a descriptive, analytical and interpretative perspective, a comparison is proposed between Brazil in the 1960s and 2020. Different contexts that mirror each other, the military dictatorship and the Bolsonaro government, nostalgic for the leaden years. Launched as an audiovisual in the streaming universe in 2020, Narciso em Vacation brings an event that occurred in 1968, which was already portrayed in a book printed in 1997, written and now narrated in front of the cameras by the protagonist of the story (and of this article), Caetano Veloso, who calls himself a Narcissus. Arrested by the dictatorship, Caetano discovered, on the eve of the documentary, that his dissident body was also the alleged reason for his imprisonment, a body described in the military records as “devirilizing”, that is, non-masculine, which subverts the binary limits of gender. and sexualities normalized by social standards. A body that, to this day, over 80 years old, continues to generate aesthesia, recognition and resistance.